Bioactive Properties and Phenolic Profile of Bioaccessible and Bioavailable Fractions of Red Radish Microgreens After In Vitro Digestion - Dorota Sosnowska; Małgorzata Zakłos-Szyda; Dominika Kajszczak; Anna Podsędek (Molecules, 2025)
The health-promoting activity of radish microgreens after consumption depends on their bioaccessibility and bioavailability. In this study, we compared the composition of phenolic compounds, their cytoprotective and anti-inflammatory activities in cell lines, and antioxidant properties of the undigested radish microgreens with their fractions obtained after simulated in vitro digestion in the stomach, as well as in the small and large intestine. The results have demonstrated higher levels of total phenolics (by 70.35%) and total hydroxycinnamic acids (3.5 times increase), an increase in scavenging efficiency toward ABTS•+ and superoxide anion radicals, and an increase in the reduction potential (FRAP method) in the gastric bioaccessible fraction. In contrast, small intestinal digestion negatively affected phenolic content (a reduction of 53.30–75.63%), except for total hydroxycinnamic acids (3-fold increase). Incubation of the non-bioavailable fraction with bacterial enzymes led to further degradation. Undigested microgreens had no negative impact on Caco-2, HT-29, and SH-SY5Y cells’ metabolism at 0.05–2 mg/mL, while all digested samples at 1 mg/mL revealed their cytotoxic potential. All samples used at a non-cytotoxic concentration showed protective activity against H2O2 and corticosterone-induced oxidative stress generation as well as reduced proinflammatory cytokines production. Overall, radish microgreens may exhibit a broad spectrum of biological activities when consumed.